2020
DOI: 10.5021/ad.2020.32.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recalcitrant Viral Warts with Combination Therapy of Systemic Acitretin and Diphenylcyclopropenone Immunotherapy

Abstract: Viral warts are benign proliferations of the epithelium caused by human papilloma virus (HPV) infection. Diverse therapeutic options are available for viral warts, depending on extension and severity of the disease. We report a case of a 19-year-old man who presented with multiple viral warts on hands and feet for 5 years. He was treated at other clinics before visiting our hospital, but there was no improvement. We treated the lesions with a combination therapy of systemic acitretin and diphenylcyclopropenone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…22 Previous research indicates that DPCP is a successful and well-tolerated therapy for resistant common warts. 7 This is the first report to compare the effect of topical DPCP versus topical podophyllin for treating anogenital warts. We chose DPCP due to its proven efficacy on common warts, but we found no randomized trials in its use in AGWs, despite its previous success in a few case reports.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…22 Previous research indicates that DPCP is a successful and well-tolerated therapy for resistant common warts. 7 This is the first report to compare the effect of topical DPCP versus topical podophyllin for treating anogenital warts. We chose DPCP due to its proven efficacy on common warts, but we found no randomized trials in its use in AGWs, despite its previous success in a few case reports.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research indicates that DPCP is a successful and well-tolerated therapy for resistant common warts. 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 As well, after 6 months of treatment with a conjunction of systemic acitretin and diphenylcyclopropenone (DPCP) immunotherapy, a 19-year-old man with multiple viral warts showed a significant improvement during the 12th week of therapy. 22…”
Section: Oral Retinoidmentioning
confidence: 99%
“…54 Combination of systemic treatment with the topical and intralesional treatment in several studies showed better response than monotherapy. 14,15,22,24 Systemic treatment in wart in pregnancy will be modified and scheduled according to safe tables of dermatologic medications in pregnancy and lactation. 55,56 Studies also showed high curing response in children.…”
Section: Acupuncturementioning
confidence: 99%